Response of siliceous marine organisms to the Permian-Triassic climate crisis based on new findings from central Spitsbergen, Svalbard ... - Foster, William (Zenodo, 2023)
Table S2 is the spreadsheet with the identifications of each radiolarian specimen. Table Abundance dataset is the abundance of each radiolarian species in the three investigated samples. ...